Rapid glacier retreat and downwasting throughout the European Alps in the early 21st century - Sommer, Christian; Malz, Philipp; Seehaus, Thorsten; Lippl, Stefan; Zemp, Michael; Braun, Matthias (Nature Communications, 2020)
Mountain glaciers are known to be strongly affected by global climate change. Here we compute temporally consistent changes in glacier area, surface elevation and ice mass over the entire European Alps between 2000 and 2014. We apply remote sensing techniques on an extensive database of optical and radar imagery covering 93% of the total Alpine glacier volume. Our results reveal rapid glacier retreat across the Alps (−39 km² a−1) with regionally variable ice thickness changes (−0.5 to −0.9 m a−1). The strongest downwasting is observed in the Swiss Glarus and Lepontine Alps with specific mass change rates up to −1.03 m.w.e. a−1. For the entire Alps a mass loss of 1.3 ± 0.2 Gt a−1 (2000–2014) is estimated. Compared to previous studies, our estimated mass changes are similar for the central Alps, but less negative for the lower mountain ranges. These observations provide important information for future research on various socio-economic impacts like water resource management, risk assessments and tourism.
CRIS-Team Scopus Importer:2020-07-03